A consistent framework for coupling modern reservoir flow simulator with mechanics. Issue 1 (August 2021) - Ferrari, A.; Pizzolato, A.; Petroselli, S.; Monaco, S.; Ottaviani, D.
Abstract: This work presents a numerical framework, for the analysis of coupled fluid and geomechanical processes related to subsurface operations, built upon ABAQUS of SIMULIA, an industrial-standard software for mechanical analysis, and Echelon, a GPU-based reservoir simulator. By using porosity updates, the proposed framework can address both the impact of pore pressure changes on rock compaction as well as the the feedback of skeleton deformations on multiphase flow. Our solution is validated by means of various test cases. The results agree with analytical and reference solutions, showing that the proposed implementation of the iterative algorithm correctly accounts for strong coupling between mechanics and flow in porous media.